Influence of Material Quality, Shopping Experience and Customer Reviews on the Interest in Buying Shoes Ventela among Generation Z - Wahid, Muklas Sarifudin; Hakimah² , Ema Nurzainul; Bhirawa, Sigit Wisnu Setya (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study is to find out the influence of material quality, shopping experience and customer reviews on the buying interest of generation Z consumers in choosing Ventela shoes. Design/Methode/Approach : This study uses a quantitative approach with primary data obtained from questionnaires. The number of respondents in this study was 40 obtained using the purposive sampling technique. Multiple linear regression analysis as a technique to explore the problems in this study, accompanied by a test-t. Research Finding : In this study, material quality and shopping experience have a significant effect on the interest in buying Ventela shoes, while customer reviews do not have a significant effect. As for the three variabel as a whole, they have a significant influence of 54.2% on buying interest. Theoretical contribution/Originality : But for Generation Z, customer reviews are very close and tend to use digital marketing, but customer reviews as a feature of online shopping do not have a significant effect. Practitionel/Policy implication : The findings in this study are that Ventela needs to improve material quality and shopping experience, while customer reviews also need to be managed properly to build trust. Research limitation : The limitation in this study is that the number of samples is too small and only examines 3 variables that are considered in the interest in purchasing a product